Transgenerational regulation of cbln11 gene expression in the olfactory rosette of the European sea bass (Dicentrarchus labrax) exposed to ocean acidification. (July 2020) - Mazurais, David; Servili, Arianna; Noel, Cyril; Cormier, Alexandre; Collet, Sophie; Leseur, Romane; Le Roy, Maelenn; Vitré, Thomas; Madec, Lauriane; Zambonino-Infante, José-Luis
Abstract: Elevated amounts of atmospheric CO2 are causing ocean acidification (OA) that may affect marine organisms including fish species. While several studies carried out in fish revealed that OA induces short term dysfunction in sensory systems including regulation of neurons activity in olfactory epithelium, information on the effects of OA on other physiological processes and actors is scarcer. In the present study we focused our attention on a European sea bass ( Dicentrarchus labrax) sghC1q gene, a member of the C1q-domain-containing (C1qDC) protein family. In vertebrates, C1qDC family includes actors involved in different physiological processes including immune response and synaptic organization. Our microsynteny analysis revealed that this sghC1q gene is the orthologous gene in European sea bass to zebrafish (Danio rerio) cbln11 gene. We cloned the full length cbln1 1 mRNA and identified the different domains (the signal peptide, the coiled coil region and the globular C1q domain) of the deduced protein sequence. Investigation of mRNA expression by qPCR and in situ hybridization revealed that cbln11 gene is especially expressed in the non-sensory epithelium of the olfactory rosette at larval and adult stages. The expression of cbln1 1 mRNA was analysed by qPCR in the first generation (F0) of European sea bass broodstock exposed since larval stages to water pH of 8.0 (control) or 7.6 (predicted for year 2100) and in their offspring (F1) maintained in the environmental conditions of their parents. Our results showed that cbln1 1 mRNA expression level was lower in larvae exposed to OA then up-regulated at adult stage in the olfactory rosette of F0 and that this up-regulation is maintained under OA at larval and juvenile stages in F1. Overall, this work provides evidence of a transgenerational inheritance of OA-induced up-regulation of cbln11 gene expression in European sea bass. Further studies will investigate the potential immune function of cbln11 gene and the consequences of these regulations, as well as the possible implications in terms of fitness and adaptation to OA in European sea bass. Highlights: Cbln1 1 mRNA is mainly expressed in the olfactory rosettes and in the gills of European sea bass. Cbln1 1 mRNA expression is localized in the non-sensory epithelium of the olfactory rosettes. Long term exposure to ocean acidification induces a stimulation of cbln1 1 mRNA expression in the olfactory rosette. Ocean acidification-induced stimulation of cbln1 1 mRNA expression suggests a regulation of innate immune function.